The European blockchain centers - Markus Demary; Vera Demary (Institut der deutschen Wirtschaft (IW), 2021)
Blockchain companies have sprung up all over Europe, at the forefront: Malta and Estonia. Compared to the sizes of their workforce, both countries have an outstanding number of blockchain companies and can easily compete with larger countries like Germany or France. The reason for this is a combination of having agglomerations, a good access to venture capital and an attractive framework for new companies.
Keywords: 330